Sustainable Finance and Digital Innovation: Synergies for Achieving SDGs in Emerging Economies - Imron Natsir; Omar Al-Fahim; Rasha Al-Ansari (Journal Markcount Finance, 2025)
Emerging economies face increasing pressure to accelerate progress toward the Sustainable Development Goals (SDGs) while confronting structural financing gaps and uneven technological capacity. Sustainable finance frameworks have expanded rapidly in these regions, yet their effectiveness depends increasingly on the integration of digital innovation capable of enhancing transparency, efficiency, and financial inclusion. This study aims to analyze the synergistic interaction between sustainable finance instruments and digital technologies, and to assess how such integration supports SDG achievement in emerging economies. A mixed-methods approach was employed, combining policy analysis, secondary financial data, and stakeholder interviews across selected emerging markets. Findings reveal that digital platforms—such as blockchain-based reporting, mobile financial services, and AI-driven risk assessment—significantly strengthen the governance and scalability of sustainable finance initiatives. The results further show that digital innovation enables more accurate impact measurement, broadens access to green financing, and improves capital mobilization for sustainability projects. The study concludes that the convergence of sustainable finance and digital innovation creates a transformative pathway for accelerating SDG progress, particularly in economies facing institutional constraints. Strengthened regulatory alignment and cross-sector collaboration are essential to maximize long-term developmental outcomes.